2012
DOI: 10.1128/aem.00794-12
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Methodology for Selective Detection of Viable Escherichia coli O157:H7 Cells by Targeting Z3276 as a Genetic Marker

Abstract: The goal of this study was to develop a sensitive, specific, and accurate method for the selective detection of viable Escherichia coli O157:H7 cells in foods. A unique open reading frame (ORF), Z3276, was identified as a specific genetic marker for the detection of E. coli O157:H7. We developed a real-time PCR assay with primers and probe targeting ORF Z3276 and confirmed that this assay was sensitive and specific for E. coli O157:H7 strains (n ‫؍‬ 298). Using this assay, we can detect amounts of genomic DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 39 publications
3
64
0
Order By: Relevance
“…Our studies of these sequences demonstrated this fact (see below). Recently a study on the expression of Z3276 along with stx2, in different growth phases showed that the expression of Z3276 increased more than 10 times in stationary phase and the pattern of Z3276 expression was similar to that of the stx2 gene [43]. Pathogenicity of bacteria causes by several virulence factors.…”
Section: Analysis and Distribution Of Z3276 Genementioning
confidence: 98%
See 1 more Smart Citation
“…Our studies of these sequences demonstrated this fact (see below). Recently a study on the expression of Z3276 along with stx2, in different growth phases showed that the expression of Z3276 increased more than 10 times in stationary phase and the pattern of Z3276 expression was similar to that of the stx2 gene [43]. Pathogenicity of bacteria causes by several virulence factors.…”
Section: Analysis and Distribution Of Z3276 Genementioning
confidence: 98%
“…Pathogenicity of bacteria causes by several virulence factors. Production of Stx is the main virulence feature of E. coli O157:H7 but it cannot be solely responsible for full pathogenicity [43]. For instance, the interaction of intimin with its receptor on host cell surface causes the formation of A/E lesions, which are most important for colonization and thus pathogenesis of this bacterium [44].…”
Section: Analysis and Distribution Of Z3276 Genementioning
confidence: 99%
“…Another issue in the development of molecular detection methods is the ability to distinguish dead from viable cells (31). This is not a crucial evaluation for this method, since a preenrichment step will be used to amplify the E. coli O157 population.…”
Section: Resultsmentioning
confidence: 99%
“…PCR/qPCR may rapidly detect presumptive Salmonella directly or after the pre-enrichment stage; ii) high sensitivity and specificity [43, [49][50][51]; and iii) the potential to amplify lower number of organisms and nonculturable bacteria. The disadvantages of PCR assays include: i) a need for thermal cycling instrument and trained personnel; ii) the potential inhibitors in food matrices may hamper PCR amplification [52]; iii) the LOD is approximately10 2 cells/reaction for qPCR.…”
Section: Pcr and Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%